ANALISIS KEBUTUHAN MODEL PEMBELAJARAN KONTEKTUAL AKSARA HAN BERBASIS WEBSITE (BAGI GURU BAHASA MANDARIN SMA/SMK/MA) - Mulawarni Mulawarni; Emzir Emzir; Ratna Dewanti (Kantor Bahasa Provinsi Maluku Utara, 2019)
This study aims to describe the needs of the Han script contextual learning model for SMA/SMK/MA Chinese Language teachers in Mandarin teacher training conducted by PPPPTK Language. This research uses the ADDIE model development approach, with steps to review the literature, provide instruments to 35 Mandarin teachers, and interview with peers. The data obtained analyzed as the main material in developing teaching materials in the learning model. Data analysis of this research is quantitative. The needs analysis shows that from 35 teachers, there are 50 % bachelor, 33 % diploma, and 17 % masters. Meanwhile, there are 61 % of teachers who have a background in Chinese language and literature, 6 % have a Mandarin education, and the rest other than Mandarin. Besides, 27 teachers claim that online learning is suitable for teachers because they are not bound by distance and time, 35 teachers state that is a need for learning model that combines the concepts of knowledge and experience, and 33 teachers also claim that contextual learning models are suitable for use in Han script material. Furthermore, there are 23 teachers stated that the origin of Han script is important, 24 people stated that the structure and components of Han script are important to be mastered, 25 people stated that the formation of words from the Han script and writing rules according to standards became the standard of competence required to be mastered by Mandarin teachers, and 17 people answered the importance of culture in learning Han script.